Don't feed the babysitter to your boa constrictor : 43 ridiculous rules every kid should know - Zemke, Deborah (New York Sterling Pub., 2006)
"Discusses rules that are so ridiculous you will never follow them."--From source other than the Library of Congress
"Level 4, more than 300 words"--Cover.
"Grades 3 and up, ages 8 and up"--P. [4] of cover.
Keywords: Conduct of life -- Juvenile humor; Conduct of life -- Humor